WHISTLEBLOWING PELECEHAN SEKSUAL DI TEMPAT KERJA: DIFERENSIASI ANTARA PRIA DAN WANITA - Yovita Mumpuni Hartarini; Sopi; Ignatius Hari Santoso (Jurnal Manajemen, 2022)
The purpose of this study was to examine the effect of job insecurity and organizational citizenship behavior on the intention to become whistleblowing. To obtain sufficient statistical results, this research uses 48 respondents who have knowledge of cases of sexual harassment that occurred in the organization where they work. To examine the relationship between constructs and the potential differences in perceptions that exist, the researchers used a path analysis technique assisted by the Smart PLS version 3. The results showed that the constructs of job insecurity and organizational citizenship behavior had a significant impact in shaping intentions to become whistleblowers in cases of sexual harassment in Indonesia. organization where they work. However, there are differences in perception between male and female workers in reporting these acts of sexual harassment Keywords: sexual harassment; job insecurity; whistleblowing; organizational citizenship behavior